Training on Creating Learning Modules for Teachers - Rulianto Rulianto; Ni Wayan Oka Yanti; Kadek Suma Yanti (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Assisting teachers in developing innovative modules is crucial for optimizing the government's policy on independent learning as expected. The Mahasaraswati University Denpasar service team supported teachers using the Brainstorming, Exploring, Talking about, and Playing (BETA) method, combining lectures and demonstrations. This activity aims to guide teachers in producing teaching modules students can use. The service results showed that 85% of the teachers successfully created learning modules in their respective fields, while 15% still needed more time to complete their modules. Based on a Likert scale questionnaire, participant satisfaction with the team's performance in assisting was as follows: 0 very dissatisfied, two dissatisfied, 20 satisfied, and 12 very satisfied. Based on the above data, the module creation training for teachers is effective and very positive to continue and improve.